Influence of random point defects introduced by proton irradiation on critical current density and vortex dynamics of Ba(Fe0.925Co0.075)2As2 single crystals - Haberkorn, Nestor Fabian (2012)
In this work we analyze the influence of random point defects introduced by 3 MeV proton irradiation on the critical current density (Jc) and vortex dynamics of a Ba(Fe0.925Co0.075)2As2 single crystal. The results show that at low temperatures (T) the irradiation produces an enhancement of Jc of up to 2.6 times. However the Jc (T) retention at different magnetic fields (H) in the elastic regime, estimated by the n exponent in Jc vs (1-(T/Tc)2)n, is poorer after the irradiations, due to the thermal softening of the pinning by the random point defects. We found that the elastic to plastic crossover and melting lines are only affected by the reduction of the superconducting critical temperature (Tc); they are exactly the same after rescaling the phase diagram by T/Tc. The pinning mechanisms in the single crystals can be associated with a mixed pinning landscape that produces a modulation in S(H,T) as a consequence of a fishtail or second peak in the magnetization.